Minimum wages, de facto private standards, and trade diversion in horticulture - Marlies Piek; Dieter von Fintel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
The effects of minimum wages on workers and firms depend on enforcement and compliance. While most research examines local determinants, this paper explores whether international market enforcement influences minimum wage impacts. In South Africa farmers exporting to the EU must comply with private standards mandating minimum wage adherence. Using difference-in-differences and administrative tax data, we analyse how a large agricultural minimum wage increase affected export stance, employment, and wages under varying private standards. Farmers did not exit export markets, but those with the EU as a secondary market temporarily diverted trade, raised wages, and maintained employment. In contrast, farmers primarily exporting to the EU increased wages more aggressively to comply but temporarily slowed employment growth. These findings suggest that international private standards play a key role in enforcing minimum wages and shaping firms' wage and employment decisions.
Keywords: J38; K42; F14; L15; 330; minimum wages; private standards; trade diversion; employment; wages; administrative tax data; South Africa